(untitled) (Bangladesh Journal of Physiology and Pharmacology, 2014)
Thalassaemia is the most common hereditary disorder in the world including Bangladesh. Beta thalassaemia major and Hb-E thalassaemia both are common in our country. Iron overload causes most of the mortality and morbidity associated with thalassaemia. To assess the iron overload and liver function a cross sectional comparative study carried out in the Department of Biochemistry, Dhaka Medical College, Dhaka in collaboration with Thalassaemia Center and Department of Pathology, Dhaka Shishu Hospital, Dhaka during the period of July 2006 to June 2007. The study was carried out with the patients who visited regularly in Dhaka Shishu Hospital Thalassaemia Centre (DSHTC) and have multiple transfusions (more than five) and the age more than 2 years. To compare the state of liver function individuals normal healthy persons were also included. Total 70 subjects were included in this study. The study subjects were distributed into two groups, the group A (cases) and group B (healthy controls). Group A consisted of 40 thalassaemia patients and group B consisted of 30 healthy individuals. According to the major types of thalassaemia present in our country, group A again divided into two, group AI patients of â-thalassaemia major included 12 patients and group AII patients of Hemoglobin E âthalassaemia included 28 patients. Prothrombin time. A statistically significant mean difference of prothrombin time was found indicating patients of thalassaemia had higher prothrombin time than normal healthy individuals (p <0.001). A statistically insignificant mean difference of prothrombin time was found indicating group AI and patients AII had no difference in prothrombin time (p > 0.05). Pearsons Correlation between prothrombin time of patients in seconds and serum ferritin of in ng/ml had studied in two ways as a whole correlation between prothrombin time of all the patients in second and serum ferritin of patients in ng/ml had r value 0.39 was statistical significant (P <0.05). On the other side correlation between prothrombin time of the patients of Group Al in second and serum ferritin of same patients in ng/ml had r value of 0.17 was signficant (P<0.05). But correlation between prothrombin time of the patients of group II in second and serum ferritin of same patients in ng/ml had r value 0.46 was statistically significant (p < 0.05). A statistically significant mean difference of ferritin was found indicating ferritin of group AI had higher level of ferritin than group AII. (p < 0.05). http://dx.doi.org/10.3329/bjpp.v26i1-2.19959 Bangladesh J Physiol Pharmacol 2010; 26(1&2) : 10-15